2014
DOI: 10.1016/j.jbiotec.2014.07.090
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms involved in the control of CYP6M2 gene in insecticide resistant in Anopheles gambiae (Diptera: Culicidae)

Abstract: Cytochrome P450s, including CYP6M2 gene, are involved in the detoxification of permethrin. Some of these genes are regulated by CnCC / dKeap 1 and Spineless / Tango in Drosophila melanogaster. This mechanism is yet to be identified in Anopheles gambiae. Thus, we examine whether there is differential regulation of CYP6M2 gene between permethrin resistant Tiassalé and susceptible Kisumu strains of An. gambiae. Bioinformatics analysis was used to search for cis-acting elements within CYP6M2 (896 bp) region hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 223 publications
(352 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, AhR/ ARNT and Nrf2/Keap 1 display a multilevel crosstalk where the latter is also a target of the former [22][23][24]. Previous studies also revealed the orthologs to Aryl hydrocarbon receptor/(AhR) Aryl hydrocarbon nuclear receptor (ARNT) and Nuclear factor erythroid factor 2 (Nrf2)/ Kelch-like associated protein 1(Keap 1) in Drosophila melanogaster to be Spineless (Ss)/Tango (Tgo) and Cap 'n' collar isoform C (CnCC)/ Drosophila Kelch-like ECH-associated protein 1 (dKeap 1) respectively [25][26][27][28]. Therefore, to understand the mechanism by which these P450s are regulated in Drosophila melanogaster (an insect model) the basics underpinning this regulation are described below:…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, AhR/ ARNT and Nrf2/Keap 1 display a multilevel crosstalk where the latter is also a target of the former [22][23][24]. Previous studies also revealed the orthologs to Aryl hydrocarbon receptor/(AhR) Aryl hydrocarbon nuclear receptor (ARNT) and Nuclear factor erythroid factor 2 (Nrf2)/ Kelch-like associated protein 1(Keap 1) in Drosophila melanogaster to be Spineless (Ss)/Tango (Tgo) and Cap 'n' collar isoform C (CnCC)/ Drosophila Kelch-like ECH-associated protein 1 (dKeap 1) respectively [25][26][27][28]. Therefore, to understand the mechanism by which these P450s are regulated in Drosophila melanogaster (an insect model) the basics underpinning this regulation are described below:…”
Section: Introductionmentioning
confidence: 99%